Cognitive and personality predictors of trait resilience in young people with psychosis proneness: an exploratory study. Issue 3 (3rd July 2022) - Mętel, Dagmara; Cechnicki, Andrzej; Arciszewska-Leszczuk, Aleksandra; Pionke-Ubych, Renata; Krężołek, Martyna; Błądziński, Piotr; Frydecka, Dorota; Gawęda, Łukasz
ABSTRACT: Background: Resilience has been increasingly recognized as a relevant area of research and clinical intervention in mental health. Although resilience is considered a putative protective factor against psychopathology development, its role in psychosis continuum disorders has been less frequently recognized. Aims: To examine neurocognitive and personality underpinnings of resilience in individuals prone to psychosis. Methods: 92 young adults were assessed with the battery of cognitive tests, TCI, CES-D, CAARMS, PQ-16, and CD-RISC-10. Linear regression was conducted to check, if resilience predicted the level of psychopathology. Correlational analysis was conducted to verify the relationships of resilience with neurocognitive and personality measures. A hierarchical multiple regression model was built to explain the predictors of resilience. Results: Lower resilience predicted higher severity of the total CAARMS score, but was not related to positive symptoms. Cognition, personality, and depressive symptoms affected resilience. The strongest predictor of resilience was the severity of depressive symptoms. Discussion: Interventions buffering resilience for psychosis-prone individuals should include therapeutic work on ego-strength and tasks mastering cognitive flexibility.